Can training offered to shopping mall employees improve their knowledge about disability and perceived self-confidence in interacting with persons presenting various limitations? - Rochette, Annie (Cogent social sciences, 2017)
Background: Social models of disability support environmental factors as major determinants of participation. The social environment can act as a facilitator for people with disability. The purpose was to explore if a training offered to shopping mall employees can improve their knowledge about disability and perceived self-confidence in interacting with persons presenting various limitations. Methods: A quasi-experimental design with pre and post-training and 3-month follow up measures with a control group. Participants were employees of a shopping mall working at least 3-shifts/week. Outcome was a quiz type questionnaire developed with experts to measure knowledge about disability and self-confidence in interacting with clients with various limitations. Non parametric statistics were used. Results: Whereas the control group (n = 11) did not show significant differences in scores for either knowledge about disability (p = 0.40) or self-confidence in interacting with people with disability (p = 0.37), the experimental group (n = 7) improved in knowledge (p = 0.009) and in self-confidence (p = 0.03) when comparing scores before training with post-training and three months later. Conclusion: These results suggest a 3-h training, including theory and experimentation of what it feels like to live with a disability, increased knowledge levels and perceived confidence of shopping mall employees in interacting with this clientele.